Analisis Faktor Determinan Pemberian ASI Eksklusif di Kecamatan Ciseeng Kabupaten Bogor - Fenita Purnama Sari Indah; Ratumas Ratih Puspita; Rita Dwi Pratiwi; Fildza Anindya Fadhila (Edu Masda Journal, 2020)
According to data collected international baby food action network ( IBFAN ) breastfeeding exclusive coverage in indonesia th stage bottom three of 51 countries in the world and 42 %, in west java breastfeeding namely the exclusive 35,3 %, in bogor District breastfeeding namely the exclusive 50,7 %, and in Sub district of Ciseeng breastfeeding there is scope exclusive 13,8 %. The Objective of this research was identified faktor-faktor relating to the exclusive breastfeeding in infants in Sub district of Ciseeng, Bogor Districts.This research is analytic using design cross sectional, with the quantitative.Respondents women who have the babies 6-24 months old in Sub district of Ciseeng, Bogor Districts some 85 people. The results of the study or the factor that there was no connection significant by the provision of exclusive breastfeeding is the age of mother ( p value 0,406 ) and education mother ( p value 0,603 ) .While , a factor that deals with the provision of exclusive breastfeeding in kecamatan ciseeng bogor districts is a capital work ( p value0,000 ) , knowledge mother ( p value 0,013 ) and support of husbands p value 0,000 ) .The experimental work on this is the conclusion there are welfare between a capital work relationship , knowledge and support mother husband by the provision of exclusivebreastfeeding on the baby in Sub district of Ciseeng, Bogor Districts.